Gambaran Pengetahuan Ibu Tentang Karies Gigi Pada Anak Usia 3-12 Tahun - La Saudi; Rahmah Nurul Aini; Siti Nadiroh (Politeknik Karya Husada, 2021)
ABSTRACT Background: knowledge and the role of parents are very important in underpinning the formation of behaviors that support or not regarding children's dental and oral hygiene. The Global Burden Of Disease Study reports that dental and oral health problems, especially dental caries, are diseases experienced by the world's population, where this condition occurs in almost half of the population (3.58 billion people). Objective: This study aims to describe the knowledge of mothers about dental caries in children aged 6-12 years. Methods: the research design used is a quantitative descriptive design. The sampling technique used was consecutive sampling, with a total sample of 73 respondents. The analysis used is univariate analysis. Data were collected online using Jotform and processed using Microsoft Excel and SPSS version 23. Results: in this study, the results showed that most of the mothers were categorized as having good knowledge as many as 49 respondents (67.1%) and mothers who had moderate knowledge as many as 13 respondents (17 ,8%) while mothers who have poor knowledge are 11 respondents (15,1%). Conclusion: mother's knowledge is very important to prevent dental caries in children and good attitudes and behavior are needed towards children's dental and oral health in order to provide optimal health education. Key Words: Child, Mother, Dental Caries, Knowledge